Carriers escape mechanisms in shallow InGaAs/GaAs quantum wells grown on vicinal (001) GaAs substrates - Tabata, A. [UNESP]; Martini, S.; Quivy, A. A.; Ceschin, A. M.; Leite, J. R. (Elsevier, 1999)
We used photoluminescence spectroscopy in order to investigate the carriers escape mechanisms in In0.15Ga0.85As/GaAs quantum wells grown on top of nominal (001) and 2°-, 4°-and 6°-off (001) towards (111)A GaAs substrates. We described the escape processes using two models that fit the Arrhenius plot of the integrated PL intensity as a function of the inverse of the sample temperature. In the first model, we considered equal escape probability for electrons and holes. In the second one, we assumed that a single type of carrier can escape from the well. At high temperature, the first model fits the experimental data well, whereas, between 50 K and 100 K, the second model has to be taken into account to describe the data. We observed that the escape activation energy depends on the misorientation angle. An unusual behavior was noted when the full width at half maximum of the photoluminescence main emission was plotted as a function of the sample temperature. We showed that the escape process of the less-confined carriers drives this behavior. © 1999 Academic Press.
Keywords: Carriers escape; Photolumienscence; Vicinal substract